THE ROLE OF EXTRACURRICULAR ACTIVITIES AND THEIR IMPACT ON LEARNING PROCESS - Claudia Cordea (Annals of the University of Oradea: Economic Science, 2014)
In this paper, we will consider how the development of extracurricular activities based on entrepreneurship may assist in developing immersive, learning, which achieve the entrepreneurial experience. It explores their impact on student learning process in order to understand the extent to which such activities simulate entrepreneurial learning. The article reports one study conducted in the current academic year 2013 - 2014, which explores different forms of extracurricular activities. In terms of entrepreneurial learning student's engagement in extracurricular activities provides enhanced opportunities for 'learning by doing' through action and experience. The data show that an increased action leads to reflective practice and social learning is important for students. The article highlights the capacity of entrepreneurship education to stimulate entrepreneurial learning; illustrating the value of extracurricular activities and explaining how develop student's enterprising behaviours. Furthermore, it is very important to examine the need to develop a more enterprising approach to learning by adopting an experiential approach.